2014
DOI: 10.1063/1.4897396
|View full text |Cite
|
Sign up to set email alerts
|

Numerical study on the influence of electron cyclotron current drive on tearing mode

Abstract: Controlling tearing modes by localized current drive is explored by using numerical simulation with a set of compressible magnetohydrodynamics equations. By examining the effects of different characteristics of driven current, such as density distribution, duration time, and deposition location, it is found that a driven current with larger magnitude and more focused deposition region shows a better suppression effect on the tearing modes. Meanwhile destabilizing effects are also observed when a driven current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…3(b) that at the end of the red lines, the island width reduces to a minimum and starts to grow at a high rate. This kind of phenomenon has been observed and investigated in several works [46][47][48] and also in our former work; 45 it occurs mainly because that the driven current is relatively excessive after the instability is eliminated. Since the driven current causes that the island topology has a spatial phase shift, the O-point moves aside and the center position is replaced by an X-point pattern reconnection.…”
Section: A Evolution Of Ntms and Effects Of Eccdmentioning
confidence: 91%
See 1 more Smart Citation
“…3(b) that at the end of the red lines, the island width reduces to a minimum and starts to grow at a high rate. This kind of phenomenon has been observed and investigated in several works [46][47][48] and also in our former work; 45 it occurs mainly because that the driven current is relatively excessive after the instability is eliminated. Since the driven current causes that the island topology has a spatial phase shift, the O-point moves aside and the center position is replaced by an X-point pattern reconnection.…”
Section: A Evolution Of Ntms and Effects Of Eccdmentioning
confidence: 91%
“…The deposition locations are generally either at the X-point or at the O-point of the magnetic island, but most experimental studies indicate that O-point deposition can achieve better suppression results, which has also been confirmed in our previous study. 45 In this work, our attention is mainly focused on O-point deposition; therefore, the deposition location of external current should be distributed mainly inside the magnetic island, as shown in Fig. 1(b).…”
Section: Modelmentioning
confidence: 99%
“…In former studies it is validated that the driven current can suppress the island width both at the O and X point of the magnetic island. But the current direction in these two cases should be opposite [40,41]. Figure 1(b) shows the distribution of external driven current density at the simulation region.…”
Section: Simulation Modelmentioning
confidence: 96%
“…With the island rotation considered, modulated current drive has the advantage of higher power effectiveness compared to continuous current drive. The reason for this is that modulated current with a small duty cycle cannot provide enough suppression force, and when the duty cycle exceeds 0.7, a larger portion of current is deposited outside of the island; when the deposition center moves away from the O-point to the X-point, the driven current plays a destabilizing In the previous study we have demonstrated that without considering island rotation, the suppression ability increases with the input energy [41,42]; but if the duty cycle is too large ( ) t > 0.7 , the suppression ability is undesirable and the driven current can barely influence the outcome no matter how large it is.…”
Section: The Effects Of Modulated Current Drivementioning
confidence: 99%
“…The driven current with larger magnitude and more focused deposition region has a better suppression effect on the TM instability. The current deposition on the island O-point has better results than that on the X-point [27]. In three-dimension nonlinear full MHD toroidal model, much more accurate meaningful results are given in the real tokamak geometry, such as EAST and ASDEX-Upgrade [28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%